Smart 2Be (Smart Bin) / Ummu Wahidah Yusoff - Yusoff, Ummu Wahidah (2020)
Smart 2Be Company has a new product to be introduced to the consumers which is the smart bin. Our company is planning to supply the smart bin to make it easy for our customer to handle their waste or trash. Smart 2Be smart bin is an automatic, simple, unique with modern design aiming to busy customers managing their waste management. As we know the cost of living in a developing country is increasing, so many people take up more than one job to live comfortably. This is the reason why people are getting too busy and they sometimes forget to throw their waste or trash properly. As for the marketing strategy of the product will be included the pricing, place or distribution and promotion strategy using many mediums that could be easily reached the target market. Our product’s target market will be Malaysian citizens since our company is based in Malaysia. Our company also has set the potential customers for the product according to the type of customer groups that are interested in purchasing the product. The target buyer of the products are people age 15-64 years old and already have a job. Another target customer is people with family which is because they probably having a hard time cleaning their house with a child in the house. The product is designed to accommodate people in managing their waste properly and minimize the time need to handle the trash for busy people. The price of the product is affordable and has many benefits. Our company targets can provide needs for people and also compete with other companies to produce better technology. The management team in the company contains few sections and is led by an experienced worker to ensure the company run efficiently.